Mole's humerus speaks. A rebuttal to Furió 2016. (17th February 2017) - Bennàsar, M.; Cáceres, I.; Cuenca-Bescós, G.; Huguet, R.; Blain, H.A.; Rofes, J.
Abstract: The discovery of small, very well-defined and perfectly preserved tooth marks on the humerus of a mole, Talpa cf. europaea (TE9, Sima del Elefante, Sierra de Atapuerca, Burgos), is extraordinary. To date, no micromammal fossil is known with puncture prints produced by a bite with a clear or delimited morphology that would permit its detailed study. The exceptional character of the finding may raise questions and suspicions about alteration and taphonomic agents. However, we have evidence that both the marks in the mole humerus are due to the action of biting and that this bite corresponds to the dentition of Beremendia fissidens . After all, not only large predators bite, as this article intends to demonstrate.